Entrepreneurs: Demographic profile, who has higher chances of survival? - Aneta Ptak-Chmielewska (The International Journal of Management Science and Information Technology (IJMSIT), 2015)
The scope of this paper is to construct the demographic profile of the entrepreneur. The basic question is: who has higher chances of survival? Recently the interest in firms survival in Poland has increased significantly. To cover the need for more detailed data there was panel database used. The survey covers the five-year history of enterprises' activity and the sample covers only enterprises employing initially fewer than 50 workers. In this paper only the sample of 1518 enterprises established in 2004 was selected. Only enterprises that initially did not employ any worker were selected. Cox regression semiparametric model with time constant and time varying variables was applied. Regarding demographic characteristics of the main owner a conclusion may be drawn, that an enterprise with a highly educated owner experienced in management had a lower liquidation risk. Opposite to other studies a male owner had higher risk of failure comparing to a female owner. Also an older owner (35 years and more) had higher chances to be liquidated, which is in opposite direction than expected. However this effect is time varying. The entrepreneur with management experience increases chances of survival. If a manager succeeded in acquiring the loan for a start the success is more probable. First-year investments increased the survival chances. The first year was the most important because at that time the main drive for being on the market was observed.
Keywords: 650; enterprises survival; Cox model; entrepreneurship